Changes in the male voice at puberty. Issue 5 (1st November 1997) - Harries, M L L; Walker, J M; Williams, D M; Hawkins, S; Hughes, I A
Abstract : The changes in the male voice in relation to the biological characteristics of puberty were assessed longitudinally in 26 boys. Speaking and singing fundamental frequencies were analysed in relation to the Tanner staging of puberty, saliva testosterone levels, and the Cooksey classification of voice analysis. There were abrupt changes in voice characteristics between Tanner stages G3 and G4 and more gradually from stages C3 to C5 of Cooksey. Although testosterone concentrations were not predictive of the changes, there was a correlation with testis volume. Voice fundamental frequencies were seen to change abruptly in late puberty, in contrast with previous studies. There is a good correlation between the Tanner and Cooksey methods of classification during male puberty.